Preparation for field work and alumni’s perceptions of work competencies: A correlational study of vocational education graduates - Agisna Mar'Atana; Nurul Amira Fitriani (Privietlab, 2026)
This study aims to analyze the effectiveness of Field Work Practice (PKL) orientation in enhancing the work competencies of vocational program alumni. PKL orientation is a preparatory phase before students enter the field, covering work-related materials, professional ethics, and guidelines for conducting the practicum. This research utilizes a quantitative methodology including a descriptive-correlational framework. The sample included 39 graduates of vocational programs chosen by purposive sampling. Data were gathered by an online five-point Likert scale questionnaire and evaluated employing validity tests, reliability assessments, descriptive statistics, and Pearson’s correlation. All instrument items were considered valid. Cronbach’s Alpha scores of 0.953 for the internship preparation variable and 0.939 for the work competence variable indicate an exceptionally high degree of dependability. Descriptive analysis indicates that alumni views of internship preparation are categorized as